Public transit planning and operation modeling, practice and behavior - Ceder, Avishai (CRC Press, 2016)
This new edition offers new solutions for delivering both better services and greater efficiency, solutions which have been developed and tested by the author in over thirty years of research work with mass transit policy makers and operators all over the world.